Spontaneous dormancy of metastatic breast cancer cells in an all human liver microphysiologic system - Wheeler, S E (Br J Cancer, 2014)
BACKGROUND: Metastatic outgrowth in breast cancer can occur years after a seeming cure. Existing model systems of dormancy are limited as they do not recapitulate human metastatic dormancy without exogenous manipulations and are unable to query early events of micrometastases. METHODS: Here, we describe a human ex vivo hepatic microphysiologic system. The system is established with fresh human hepatocytes and non-parenchymal cells (NPCs) creating a microenvironment into which breast cancer cells (MCF7 and MDA-MB-231) are added. RESULTS: The hepatic tissue maintains function through 15 days as verified by liver-specific protein production and drug metabolism assays. The NPCs form an integral part of the hepatic niche, demonstrated within the system through their participation in differential signalling cascades and cancer cell outcomes. Breast cancer cells intercalate into the hepatic niche without interfering with hepatocyte function. Examination of cancer cells demonstrated that a significant subset enter a quiescent state of dormancy as shown by lack of cell cycling (EdU(−) or Ki67(−)). The presence of NPCs altered the cancer cell fraction entering quiescence, and lead to differential cytokine profiles in the microenvironment effluent. CONCLUSIONS: These findings establish the liver microphysiologic system as a relevant model for the study of breast cancer metastases and entry into dormancy.